Epigenetic Therapy Promotes the Ratio of Th1/Th17 Lineage to Reverse Immune Evasion and Treat Leukemia Relapse Post-allogeneic Stem Cell Transplantation in Non-APL AML Patients - Xi, Yang; Jingying, Dai; Chenglong, Li; Hong, Zheng; Rong, Zhang; Xiaodong, Wang; Chunsen, Wang; Xiaobing, Huang (Frontiers in Molecular Biosciences, 2021)
To reverse the early-stage relapse post HSCT, we investigated the safety and efficacy of a new epigenetic regimen (Chidamide, Decitabine, plus Thymalfasin simultaneously) on Acute myeloid leukemia (AML) patients (exclude Acute promyelocytic leukemia, APL). Twenty-four patients were enrolled in this observational study during April 2015 to May 2018. The most common adverse event was reversible CTCAE grade 2 thrombocytopenia (20/24). Strikingly, all 24 patients had response to this epigenetic regimen accompanied with decreased measurable Residual Disease (MRD). The overall survival rate is 79.2% (19/24), with the relapse-free survival rate of 79.2%(19/24). During this regimen treatment, Th1 cells and CD3+CD4-CD8+T cells increased, and Th17 cells decreased gradually. The status of high Th1 and low Th17 cells was still observed at the third months after discontinuation of this regimen. Interestingly, the significant elevated ratio of Th1/Th17 seemed to reflect the treatment-related immune effect, which maybe a valuable marker to be monitored in the early-relapse stage, for evaluating the efficacy and prognosis.